STEROIDAL SAPOGENINS 163 THE BIOGENESIS OF STEROIDALS APOGENINS IN PLANTS - MARKER, RE; LOPEZ, J (BOTANICA-MEX S. A, TEXCOCO, EM, MEX, 1947)
The biogenetic relationship of the steroidal sapogenins in the Agave specie is discussed.
J OPT SOC AM
Keywords: STEROIDAL SAPOGENINS. 163., BIOGENESIS, STEROIDALS APOGENINS, PLANTS; QUIMICA; QUIMICA INORGANICA; QUIMICA DE LOS PIGMENTOS